Do health service contacts with community health workers influence the intention to use modern contraceptives among non-users in rural communities? Findings from a cross-sectional study in Nigeria - Bola Lukman Solanke; Olufemi O. Oyediran; Abayomi Folorunso Awoleye; Oluwayemisi Elizabeth Olagunju (BMC, 2023)
Abstract Background Studies in many developing countries have shown that community health workers (CHWs) are valuable for boosting contraceptive knowledge and usage. However, in spite of the evidence, studies in Nigeria have rarely examined whether in the absence of skilled health personnel such as doctors and nurses in rural and remote communities, the health service contacts of non-users with CHWs drive the intention to use modern contraceptives. This study, therefore, examines the extent to which health service contacts with CHWs are associated with the intention to use modern contraceptives among non-users in rural communities of Nigeria. Methods This study adopted a descriptive cross-sectional design. Data were extracted from the most recent Nigeria Demographic and Health Survey (NDHS). The study analyzed a weighted sample of 12,140 rural women. The outcome variable was the intention to use modern contraceptives. The main explanatory variable was health service contacts with CHWs. Statistical analyses were performed at three levels with the aid of Stata version 14. Three multivariable regression models were estimated using an adjusted Odds Ratio (aOR) with a 95% confidence interval. Statistical significance was set at p < 0.05. Results Findings showed that more than a quarter (29.0%) of women intends to use modern contraceptives. Less than one-fifth (15.9%) of the women had health service contacts with CHWs. In Model 1, women who had health service contacts with CHWs were more likely to intend to use modern contraceptives (aOR =1.430, 95% CI: 1.212-1.687). Likewise, in Model 2, women who had health service contacts with CHWs had a higher likelihood of intending to use modern contraceptives (aOR = 1.358, 95% CI: 1.153-1.599). In Model 3, the odds of intention to use modern contraceptives were higher among women who had health service contacts with CHWs (aOR =1.454, 95% CI: 1.240-1.706). Conclusion In rural areas of Nigeria, health service contacts with CHWs are significantly associated with the intention to use modern contraceptives. Family planning programmers should leverage the patronage of CHWs for the purpose of family planning demand generation in rural areas.